Pure testicular carcinoid associated with intratubular germ cell neoplasia. Issue 12 (25th November 2005) - Merino, J; Zuluaga, A; Gutierrez-Tejero, F; del Mar Serrano, M; Ciani, S; Nogales, F F
Abstract : This case report describes for the first time a case of pure testicular carcinoid preaortic lymph node metastases in a 25 year old patient with carcinoid syndrome. The simultaneous occurrence of intratubular germ cell neoplasia in the surrounding testicular tissue was identified by OCT4 and placental-like alkaline phosphatase positivity. This confirmed that the tumour had a germ cell origin in the testis, rather than being a metastasis from an extragenital carcinoid.